2000
DOI: 10.1073/pnas.080077197
|View full text |Cite
|
Sign up to set email alerts
|

Association of Escherichia coli ribosomes with the inner membrane requires the signal recognition particle receptor but is independent of the signal recognition particle

Abstract: In mammalian cells, as well as Escherichia coli, ribosomes translating membrane proteins interact cotranslationally with translocons in the membrane, and this interaction is essential for proper insertion of nascent polypeptides into the membrane. Both the signal recognition particle (SRP) and its receptor (SR) are required for functional association of ribosomes translating integral membrane proteins with the translocon. Herein, we confirm that membrane targeting of E. coli ribosomes requires the prokaryotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
65
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 29 publications
11
65
0
Order By: Relevance
“…1B). As such, the proportion of membrane-associated ribosomes in H. volcanii is far more similar to that reported in eukaryal cells (ϳ60 -80%) (35,36) that what has been reported in Bacteria (ϳ5-10%) (37,38).…”
Section: In H Volcanii a Major Proportion Of Ribosomes Are Membranesupporting
confidence: 83%
“…1B). As such, the proportion of membrane-associated ribosomes in H. volcanii is far more similar to that reported in eukaryal cells (ϳ60 -80%) (35,36) that what has been reported in Bacteria (ϳ5-10%) (37,38).…”
Section: In H Volcanii a Major Proportion Of Ribosomes Are Membranesupporting
confidence: 83%
“…Previous studies of FtsY revealed the receptor interaction with membranebound ribosomes (Herskovits et al, 2002) and with the SecYEG translocase (Angelini et al, 2005), and showed how FtsY is regulated on the membrane by acidic lipids Braig et al, 2009;Erez et al, 2010;Parlitz et al, 2007). Other studies showed that FtsY plays a central role in vivo in ribosome targeting to the membrane (Herskovits and Bibi, 2000) and in the productive expression of IMPs Yosef et al, 2010). Taken together, it is generally accepted that FtsY functions as a membrane-associated protein, as has been shown recently (Mircheva et al, 2009).…”
Section: Introductionmentioning
confidence: 72%
“…There is biochemical evidence that membrane-bound ribosomes in E. coli are completely devoid of any physical connection with the nucleoids (46). It was also shown by independent studies that freely diffusing mRNAs are localized close to the cell periphery, where they are translated by ribosomes (19,27,28).…”
Section: Discussionmentioning
confidence: 97%